KEPATUHAN WAJIB PAJAK MENGGUNAKANAN SISTEM E-FILLING (Studi Kasus Pada Kantor Pelayanan Pajak Pratama Wilayah Bengkulu) - Ahmad Sumarlan; Fraternesi Fraternesi; Sulastri Asmita Wati (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2020)
ABSTRACTE-Filling is a way to deliver e-SPT online and in real time through the internet, the internet is a supporting media for the E-Filling system, where in using the E-Filling system a good understanding is needed. This also becomes an important factor for taxpayers to use E-Filling, because with a good internet the higher the desire of taxpayers to use E-Filling the internet is chosen as a means of supporting tax administration because with the internet the SPT submission process will be faster, safer, easier , smoothly and can be done anywhere within 24 hours, with the hope that taxpayers will be more obedient in paying taxes. The purpose of this study aims to determine the application of the E-Filling system in compliance with taxpayers registered in the Tax Office Primary. Data collection tools carried out by Observation, Interview and Documentation. Data collection techniques using Comparative Descriptive Analysis is to do a comparative analysis of compliance before and after Observation and Documentation E-Filling, by organizing data into categories broken down into units, synthesizing, organizing into patterns of choosing where is important and what is learned. Based on the results of this study indicate that the E-Filling in KPP Pratama Bengkulu in 2016-2017 increased by 2.38% and from 2017-2018 reached an increase of 7.655% while for Personal E-Filling did not increase.Keywords: E-Filling System, Taxpayer Compliance.